Considering the Impact of a 12-Week Intervention Program on Behavioral Intentions and Key Health-Related Constructs in Adolescent Basketball Players - Zhao, Jin; Sumranpat Brady, Wannaporn (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to evaluate the impact of a 12-week basketball intervention program on adolescents’ behavioral intentions and key health-related constructs, including self-efficacy, social support, situational factors, and outcome expectations, based on the social cognitive theory (SCT), focusing on each gender and comparing both genders. Materials and methods. A total of 175 adolescents (age: 12–14 years old) from basketball clubs in Guangxi Province, China, were involved in the study. The partcipants were divided by gender into two groups (male [n = 88] and female [n = 87] groups) and underwent an intervention program for 12 weeks. The validity and reliability of all measurements were tested. Regression analysis was used to identify predictors of behavioral intentions, which were used to design the intervention program. Results. The intervention significantly improved self-efficacy, social support, situational factors, outcome expectations, and behavioral intentions in both male and female adolescents. Behavioral intentions score increased from 3.19 to 3.77 for male adolescents and from 3.3 to 4.27 for female adolescents (p < 0.001). Furthermore, it was noted an increase in self-efficacy scores from 3.51 to 4.22 for male adolescents and from 3.26 to 4.23 for female adolescents (p < 0.001). Improvements in other constructs were also observed in both genders, with no significant gender differences in post-intervention outcomes (p > 0.05). Conclusions. The findings indicate that a 12-week intervention program based on the SCT effectively enhanced adolescents’ behavioral intentions and related constructs. Developing gender-specific intervention programs is important for maximizing intervention effectiveness.